Natural deep eutectic liquid and ultrasound-assisted extraction of milk thistle phenolics and their hepatoprotective activities - Nasrullah, Nabiha; Akram, Sumia; Rashid, Ayoub; Adnan, Ahmad; Mushtaq, Muhammad (Frontiers in Sustainable Food Systems, 2024)
The present research describes the utilization of Natural Deep Eutectic Liquid in combination with ultrasound for the extraction of milk thistle polyphenols. The extracts obtained under different conditions were evaluated for their in-vitro antioxidant activities and hepatoprotective activities in Albino mice (in-vivo). The extraction parameters involving liquid-to-solid ratio (S/L), ethanol to Natural Deep Eutectic liquid ratio (EtOH/DES), extraction time (t), and ultrasound treatment time were investigated and optimized to enhance the recovery of bioactives, their phenolic content, Trolox Equivalent antioxidant capacity (TEAC), and radical scavenging capacity (RSC). The extraction of milk thistle polyphenols using Glucose/Citric acid (1:1) based natural deep eutectic liquid coupled with ultrasound for 1.0 minutes under S/L of 6.2, EtOH/DES 9, and extraction time of 120.8 min offered 35.89±2.29 g/100g of crude extracts which were three folds higher than conventional solvent extraction (CSE). Each gram of milk thistle extracts obtained thus comprised 377.93±6.17 mg GAE of TPC, exhibited 298.70±3.06 µmol TEAC, 93.16±0.58 percent inhibition of DPPH free radicals. Besides, the administration of milk thistle extracts obtained above at 25 mg/Kg body weight in Albino mice significantly (p≤0.05) improved the liver function parameters at the end of treatment time (7 days). Overall, it was observed that NaDES in combination with medium-level ultrasound energy (700 watt) might work as a sustainable choice to enhance the recovery of bioactive phenolics from milk thistle powder without compromising their antioxidant and hepatoprotective potential.